SMARA JANTRA - Kadek Ayu Diah Mutiara Dewi; Ni Made Ruastiti; I Gusti Putu Sudarta (RADJA PUBLIKA, 2025)
Smara Jantra is a contemporary dance work rooted in local wisdom, reflecting a reinterpretation of Tari Telek, one of the core elements in the mepajar ritual of Desa Adat Legian, Bali. This work emerges as an aesthetic response to contemporary challenges facing the preservation of sacred values in traditional performing arts, which are increasingly confronted by the forces of tourism commodification and shifts in meaning. Tari Telek, traditionally functioning as a spiritual medium and protective symbol, has undergone transformations in function and significance over time. In response, the choreographer seeks to transform these values into a new choreographic form that remains grounded in Balinese philosophical and spiritual foundations. This creative research examines three main aspects: (1) the creative process in formulating and developing the artistic concept; (2) the choreographic form as the result of creation; and (3) the symbolic meanings and reflective messages embodied in the work. The Angripta Sesolahan method serves as the primary approach, consisting of five stages, ngarencana, nuasen, makalin, nelesin, and ngebah, derived from the philosophy of tradition-based creative work in Bali. The outcome is a site-specific performance staged at Pura Agung Legian, offering an integrated experience of space, body, and spirituality. The novelty of this work lies in the integration of the cosmological concept of luwan-teben as the foundation for a transformative aesthetic, as well as the application of a contextual local creation method within the realm of contemporary Balinese performing arts.